Research on the use of tetracaine hydrochloride jelly surface anesthesia in combination with intravenous anesthesia for pain-free cystoscopy - Bai, Wenjie; Luo, Daxun; Wurige, Mule; Xiao, Bo; Li, Jianxing (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to evaluate the efficacy and safety of tetracaine hydrochloride jelly surface anesthesia in combination with intravenous anesthesia for painless cystoscopy.MethodsThis study was conducted at the Department of Urology, Beijing Tsinghua Changgung Hospital, from 1 January 2023 to 31 December 2024. A total of 60 eligible inpatients were recruited based on predefined inclusion and exclusion criteria and were randomly allocated to two groups, each comprising 30 patients. The experimental group received tetracaine hydrochloride jelly in conjunction with intravenous anesthesia, whereas the control group received intravenous anesthesia alone. Both groups were administered a slow intravenous infusion of 1.5 mg/kg propofol (1%) and 0.15 μg/kg remifentanil. After 2 min, the experimental group received 10 mL of tetracaine hydrochloride jelly via the urethra, while the control group received 10 mL of glycerin. The surgical procedure commenced 4 min later. Throughout the procedure, patients maintained spontaneous breathing, and additional propofol was administered if necessary. Preoperative parameters, including propofol dosage, cystoscopy time, anesthesia/awakening time, and relevant vital signs, were recorded for both groups.ResultsCompared to the control group, the experimental group required significantly less additional propofol, had shorter anesthesia, cystoscopy, and surgical times, and exhibited higher postoperative SpO₂ levels. No postoperative complications or adverse events were observed in either group.ConclusionThe combination of tetracaine hydrochloride jelly surface anesthesia and intravenous anesthesia demonstrated significant advantages in painless cystoscopy, effectively reducing the additional dosage of propofol, shortening examination time, improving postoperative oxygenation, and ensuring high safety. This approach has considerable clinical value and potential for widespread application.Clinical trial registrationChiCTR2300070527, Date of registration:2023-04-14.